2022
DOI: 10.1108/rege-04-2021-0068
|View full text |Cite
|
Sign up to set email alerts
|

The role of compensation in shaping employee’s behaviour: a mediation study through job satisfaction during the Covid-19 pandemic

Abstract: PurposeThis research aimed to study the impact of compensation on employee retention and turnover intentions among healthcare employees. The study also tested the mediation role of job satisfaction in the relationship.Design/methodology/approachIn the present study, self-administrated questionnaires were distributed among 600 doctors working in public hospitals of Pakistan, following stratified sampling. The data analysis was conducted through SPSS and smart-PLS.FindingsResults of the present study supported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
1
10
0
3
Order By: Relevance
“…Additionally, companies should offer competitive compensation packages and rewards programs to increase job satisfaction and retain their talented employees. These programs should be reviewed regularly to ensure that they remain attractive and relevant (Aman‐Ullah et al, 2023), and this underscores the importance of setting clear expectations and formal job requirements and ensuring that employees fulfill their job responsibilities. Furthermore, the study highlights the need for the pharmaceutical industry to develop career growth opportunities to retain skilled and talented pharmacists in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, companies should offer competitive compensation packages and rewards programs to increase job satisfaction and retain their talented employees. These programs should be reviewed regularly to ensure that they remain attractive and relevant (Aman‐Ullah et al, 2023), and this underscores the importance of setting clear expectations and formal job requirements and ensuring that employees fulfill their job responsibilities. Furthermore, the study highlights the need for the pharmaceutical industry to develop career growth opportunities to retain skilled and talented pharmacists in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmaceutical industry in Pakistan is facing a significant brain drain due to the low compensation and rewards (Nadir et al, 2023) and career growth opportunities (Sancak et al, 2023), which has a significant impact on employee retention (Aman- Ullah et al, 2023). Akinwale and George (2023) have presented evidence that inadequate compensation and pay have demotivated healthcare professionals and workers, which leads toward low productivity, and ultimately, it is pushing them toward the global market to seek better employment.…”
Section: Introductionmentioning
confidence: 99%
“…4,[19][20][21] In the healthcare system, researchers reported that healthcare workers' turnover intention happened before the turnover behavior. [22][23][24]…”
Section: Theoretical Background and Hypothesis Development Turnover I...mentioning
confidence: 99%
“…Karyawan akan menyadari untuk menaati peraturan-peraturan yang berlaku. Gaji dengan kata lain kompensasi juga terkait dengan kepuasan kerja, semakin sesuai kompensasi yang didapatkan maka karyawan akan mendapat kepuasan kerja (Aman- Ullah et al, 2022).…”
Section: Gajiunclassified